Representasi Perempuan Dalam Sansana Bandar [Representation of Women in Urban Sansana] - Reigina Yossi, Midori; Herlijanto, Johanes (Universitas Pelita Harapan, 2024)
Representasi perempuan dalam Sansana Bandar, dengan fokus pada manuskrip cerita Sansana Bandar “Bandar Huntip Batu Api” menggunakan metode etnografi dan paradigma naratif, analisis mencakup elemen-elemen cerita yang memperlihatkan peran kompleks perempuan. Meskipun tradisi kesetaraan Gender tetap terakar dalam masyarakat Dayak, cerita ini kadang tidak selaras dengan norma lokal, menciptakan ketegangan antara budaya dan naratif. Hasilnya memperlihatkan kompleksitas budaya dan pandangan terhadap Gender di Kalimantan Tengah, menyuguhkan pemahaman mendalam terhadap cerita sebagai refleksi budaya. Dianalisis menggunakan pendekatan etnografi sebagai metodologi penelitian. Data penelitian diambil melalui wawancara, dan observasi langsung dalam masyarakat Dayak Kalimantan Tengah, memberikan pemahaman yang lebih kontekstual terhadap Representasi perempuan dalam konteks budaya lokal. Konteks budaya, terutama norma-norma Gender, turut membentuk Representasi perempuan dalam cerita, dan Teori Paradigma Naratif memberikan perspektif terkait peran Gender dalam konteks sejarah dan kultural. Representation of women in Sansana Bandar, with a focus on the manuscript of the Sansana Bandar story 'Bandar Huntip Batu Api,' utilizes ethnographic methods and narrative paradigm. The analysis encompasses elements of the story that reveal the complex roles of women. Despite the tradition of gender equality being deeply rooted in Dayak society, this story sometimes deviates from local norms, creating tension between culture and narrative. The results showcase the cultural complexity and perspectives on gender in Central Kalimantan, offering a profound understanding of the story as a cultural reflection. It is analyzed using an ethnographic approach as a research methodology. Research data is obtained through interviews and direct observations within the Dayak community in Central Kalimantan, providing a more contextual understanding of the representation of women in the local cultural context. The cultural context, especially gender norms, contributes to shaping the representation of women in the story, and the Narrative Paradigm Theory provides a perspective on the gender roles in the historical and cultural context.